Insights on the Mechanisms of the Protective Action of Naringenin, Naringin and Naringin Dihydrochalcone on Blood Cells in Terms of Their Potential Anti-Atherosclerotic Activity - Teresa Kaźmierczak; Sylwia Cyboran-Mikołajczyk; Natalia Trochanowska-Pauk; Tomasz Walski; Paulina Nowicka; Dorota Bonarska-Kujawa (Molecules)
Atherosclerosis is caused by injury to the blood arteries and progressive oxidative stress. Blood cells play an important role in its development; thus, their protection is important. Naringenin (N) is documented to possess a protective action against atherosclerosis, and we hypothesize that its derivatives, naringin (Nr) and naringin dihydrochalcone (Nd), with slightly different structures, possess similar or better activity. Therefore, this research aimed to find the mechanism of protective action of N, Nr and Nd in relation to erythrocytes, peripheral blood mononuclear cells (PBMCs) and platelets in terms of their potential anti-atherosclerotic effect. Moreover, their physicochemical properties and the interaction of flavonoids with liposomes were studied. All flavonoids protected erythrocytes from AAPH- and H2O2-induced oxidation to varying degrees. None of them had a destructive effect on erythrocyte membrane, and they did not impact the metabolic activity of PBMC and platelets. Nr and Nd inhibited collagen-induced platelet aggregation better in tested concentrations than N. Studied compounds did not induce liposome aggregation, but N and Nd changed their dipole potential. Obtained results show that Nd possesses slightly better activity than N and may have a better potential health effect on blood cells, which is very important in the design of anti-atherosclerotic therapeutics.